2015
DOI: 10.1177/0308022615581391
|View full text |Cite
|
Sign up to set email alerts
|

An occupational therapy intervention for residents with stroke living in care homes in the United Kingdom: A content analysis of occupational therapy records from the OTCH trial

Abstract: Key findings: Residents' goals focused on leisure activities whereas intervention time was mostly spent on improving function  There are conflicts between carer time constraints and supporting residents' independence to achieve therapy goals What the study has added:This study contributes further understanding about the content of an occupational therapy intervention delivered in UK care homes, including distribution of therapists' time and the goals most important to residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Also explored healthcare professional perceptions of feasibility and which patients’ intervention most suited to. Qualitative Interviews Intervention Participant responses How delivery is achieved Reach Causal mechanisms in context Contextual moderators Unintended consequences Contextual factors shaping intervention theory Yes Littlewood 2015 [ 34 ] Nichols 2017 [ 35 ] Explored experiences of patients about intervention, with focus on patient adherence, and how changed over time Qualitative Interviews (longitudinal) Intervention Participant responses Causal mechanisms in context Contextual moderators How delivery is achieved No Williams 2015 [ 36 ] Novak 2015 [ 37 ] Investigated whether and how trial sites supplied thawed plasma in a timely manner Quantitative Detailed author description Observation, reports from sites Intervention and trial Fidelity How delivery is achieved No Sands 2016 [ 38 ] Explored how the flexible complex intervention was delivered in real-world complex settings Qualitative Trial dataset Intervention How delivery is achieved Adaptations Contextual moderators Participant responses Unintended consequences Contextual factors shaping intervention theory Fidelity No Saville 2016 [ 39 ] Explored preferences and experiences of intervention deliverers about various aspects of intervention Quantitative Questionnaire Intervention How delivery is achieved No Tjia 2017 [ 40 ] Investigated patients’ perceptions of benefits and drawbacks of intervention Quantitative Questionnaire Intervention Participant responses No Vennik 2019 [ 41 ] Explored views and experiences of parents and practice nurses of intervention and usual care Qualitative Interviews …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Also explored healthcare professional perceptions of feasibility and which patients’ intervention most suited to. Qualitative Interviews Intervention Participant responses How delivery is achieved Reach Causal mechanisms in context Contextual moderators Unintended consequences Contextual factors shaping intervention theory Yes Littlewood 2015 [ 34 ] Nichols 2017 [ 35 ] Explored experiences of patients about intervention, with focus on patient adherence, and how changed over time Qualitative Interviews (longitudinal) Intervention Participant responses Causal mechanisms in context Contextual moderators How delivery is achieved No Williams 2015 [ 36 ] Novak 2015 [ 37 ] Investigated whether and how trial sites supplied thawed plasma in a timely manner Quantitative Detailed author description Observation, reports from sites Intervention and trial Fidelity How delivery is achieved No Sands 2016 [ 38 ] Explored how the flexible complex intervention was delivered in real-world complex settings Qualitative Trial dataset Intervention How delivery is achieved Adaptations Contextual moderators Participant responses Unintended consequences Contextual factors shaping intervention theory Fidelity No Saville 2016 [ 39 ] Explored preferences and experiences of intervention deliverers about various aspects of intervention Quantitative Questionnaire Intervention How delivery is achieved No Tjia 2017 [ 40 ] Investigated patients’ perceptions of benefits and drawbacks of intervention Quantitative Questionnaire Intervention Participant responses No Vennik 2019 [ 41 ] Explored views and experiences of parents and practice nurses of intervention and usual care Qualitative Interviews …”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 process evaluation studies identified, nine were quantitative [ 22 , 24 28 , 32 , 37 , 39 , 40 ] and eight qualitative [ 23 , 29 31 , 34 – 36 , 38 , 41 , 42 ]. The three labelled as process evaluations were all qualitative [ 30 , 31 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations